A systematic review and network meta-analysis of parenchymal transection techniques during hepatectomy: an appraisal of current randomised controlled trials. Issue 2 (February 2020) - Kamarajah, Sivesh K.; Wilson, Colin H.; Bundred, James R.; Lin, Aaron; Sen, Gourab; Hammond, John S.; French, Jeremy J.; Manas, Derek M.; White, Steven A.
Abstract: Background: Major liver resection can lead to significant morbidity and mortality. Blood loss is one of the most important factors predicting a good outcome. Although various transection methods have been reported, there is no consensus on the best technique. This systematic review and network meta-analysis aims to characterise and identify the best reported technique for elective parenchymal liver transection based on published randomised controlled trials (RCT's). Methods: A systematic review was conducted using MEDLINE, EMBASE, and Cochrane Central to identify RCT's up to 5th June 2019 that examined parenchymal transection for liver resection. Data including study characteristics and outcomes including intraoperative (blood loss, operating time) and postoperative measures (overall and major complications, bile leaks) were extracted. Indirect comparisons of all regimens were simultaneously compared using random-effects network meta-analyses (NMA) which maintains randomisation within trials. Results: This study identified 22 RCT's involving 2360 patients reporting ten parenchymal transection techniques. Bipolar cautery has lower blood loss and shorter operating time than stapler (mean difference: 85 mL; 22min) and Tissue Link (mean difference: 66 mL; 29min). Bipolar cautery was ranked first for blood loss and operating time followed by stapler and TissueLink. Harmonic scalpel is associated with lower overall complications than Hydrojet (Odds ratio (OR): 0.48), BiClamp forceps (OR: 0.46) and clamp crushing (OR: 0.41). Conclusion: Bipolar cautery techniques appear to best at reducing blood loss and associated with shortest operating time. In contrast, Harmonic scalpel appears best for overall and major complications. Given the paucity of data and selective outcome reporting, it is still hard to identify what is the best technique for liver resection. Therefore, further high-quality large-scale RCT's are still needed.